RANCANG BANGUN BUBU ELVER SPIRAL (Desain of Elver Spiral Traps) - Misbah Sururi; Gondo Puspito (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2014)
ABSTRACTPVC trap is used by fisherman in the southern Java Island waters to capture elver or juvenile eels measuring < 10 gr. One of some problems is how difficult the traps transportation in great quantities. This study tried to design a new trap from spiral little iron material as frame construction. The aim is toward easy tobe shorted so became simple transportation of traps. All experiments were conducted on the Fishing Gear Laboratory, Bogor Agricultural University. The study is divided into two stages, that are design of spiral traps and testing the effectiveness of a spiral trap with two pipe traps, that are elver traps modification (Sururi et al. 2014) and fisherman‘s traps as control. The entire test was conducted in the experimental tank containing between 60 elvers with 20 times repetition. The soaking time were done within 20 minutes of observation each. Spiral traps design giving simpler and easier in transporting traps, because ist weight is 0.24 kg or 3.25 time less weigh than elver traps modification and 2.16 time less weight than fisherman traps. Beside, spiral traps can be shorted to 6 cm, or 8.3 time shorter than elver traps modification and 5 time shorter than fisherman traps. The results showed that spiral traps construction caught 286 individuals or more than elver traps modification (165 individuals) and fishermen’s traps (43 individuals).Keywords: PVC traps, elver, ijep, spiral traps-------ABSTRAKBubu elver digunakan oleh nelayan di perairan selatan Pulau Jawa untuk menangkap elver atau juvenil sidat berukuran < 10 g. Salah satu permasalahannya, pengangkutan bubu dalam jumlah banyak cukup sulit dilakukan. Penelitian ini mencoba merancang bubu dari material kawat besi berbentuk spiral agar bubu dapat dipendekkan sehingga memudahkan dalam pengangkutan-nya. Penelitian dilaksanakan di Laboratorium Bahan dan Alat Penangkapan Ikan, Institut Pertanian Bogor. Kegiatan terdiri atas 2 bagian, yaitu perancangan bubu dan pengujian bubu elver spiral dibandingkan dengan bubu elver modifikasi (Sururi et al. 2014) dan bubu elver milik nelayan sebagai kontrol. Pengujian dilakukan di dalam tangki percobaan yang berisi 60 elver sebanyak 20 ulangan. Lama perendaman bubu 20 menit per ulangan. Bubu elver spiral lebih simpel dan mudah dalam pengangkutannya, karena berat bubu hanya 0,24 kg atau 3,25 kali lebih ringan dari bubu elver modifikasi dan 2,16 kali lebih ringan dari bubu elver standar. Selain itu, bubu elver spiral juga dapat dipendekkan hingga 6 cm, atau 8,3 kali lebih pendek dari bubu elver modifikasi dan 5 kali lebih pendek dari bubu elver standar. Berdasarkan hasil pengujian, bubu elver spiral memerangkap elver sejumlah 286 ekor, atau lebih banyak dibandingkan dengan bubu elver modifikasi 165 ekor dan bubu elver standar 43 ekor.Kata kunci: Bubu elver, elver, ijep, bubu spiral